PUBLIC COMMUNICATION DALAM DAKWAH ISLAM - Uus Uswatusolihah (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2010)
The lecture is one of the methods of propaganda that has been practiced since the inception of Islam.Although the current mission has undergone rapid development and change, but this method of preaching still exist in anIslamic society. This is because although the lecture method is considered less effective, but the lecture method has its ownadvantages and privileges compared to other methods. One effort to become more effective lecture is to apply thetheories and principles in public communication. Because the terms of the communication process, religious lectures areessentially public communication as well, differing only in the content of the message and purpose